Penentuan Jumlah Produksi Ayudes menggunakan Fuzzy Tsukamoto - Lusye Bakarbessy; Doms Upuy; Arlene Henny Hiariey (Program Studi Matematika FMIPA Universitas Pamulang, 2023)
CV Abadi Tiga Mandiri Ambon as one of the companies producing goods in the form of 'Ayudes' branded drinking water in the city of Ambon. The production of bottled water that the company has been doing so far depends on the number of existing requests. However, with an uncertain number of requests each month, it is difficult for the company to determine the amount of production that should be produced. This study aims to predict the amount of bottled water production to meet consumer demand using the Fuzzy Tsukamoto Method. The results of the study using the Tsukamoto Fuzzy Method using the